PENGARUH CAPITAL INFLOW DAN CAPITAL OUTFLOW DI INDONESIA TERHADAP NILAI TUKAR RUPIAH - Kristopel F Tambunan; Syarief Fauzie (Departemen Ekonomi Pembangunan USU, 2014)
The purpose of this study is to know how is the effect of capital inflow and capital outflow in Indonesia against the rupiah exchange rate in short-term and long-term. Variables which are used in capital flow are direct investment, portofolio investment and other investment, that recorded in the Indonesian balance of payments on capital transaction and financial account. The estimation result of the short-term equation indicates that the enhancement of direct investment inflow at the last quarter caused the rupiah exchange rate run into appreciation. While the other investment inflow at the last two quarters, direct investment outflow at one or two quarters and portfolio investment outflow at the last quarter caused the rupiah exchange rate run into depreciation. The estimation results of the long-term equation indicates that the enhacement of other investment inflow caused the rupiah exchange rate run into appreciation, portfolio investment outflow and other investment outflow caused the rupiah exchange rate run into depresiation.Keywords: Exchange Rate Rupiah, Capital Inflow, Capital Outflow